Analisis Daya Dukung dan Kapasitas Tampung Pada Rencana Pengembangan Kawasan Agrokawista Pongangan - Paskhalis Bonnieaaron Timoro; Dhiyan Khrisna Wardhani; R Clarrino Adesetya Jaya (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Tourism development has a positive impact on the economic growth of a region. This development is shifting towards sustainable tourism, one of which is village tourism. The development of village tourism is based on the tourism potential of a region. Kelurahan Pongangan is one of the areas striving to develop village tourism and already has a development plan. However, this plan has not yet gone through the stages of carrying capacity analysis and capacity assessment. The objective of this study is to analyse the consistency of carrying capacity and capacity assessment with the characteristics of tourism potential. The research uses quantitative research methods with a descriptive approach. Data collection methods include interviews, direct observation and literature review. The collected data will be analysed using carrying capacity analysis and capacity assessment techniques. The presentation of data in this research is descriptive. The analysis shows that the carrying capacity of Agrokawista Pongangan area is 148 people, and the capacity of mushroom and bonsai cultivation buildings is insufficient. In addition, the capacity of infrastructure, such as drainage, does not meet requirements. The inadequate capacity requires a reassessment of the size of the existing buildings